The level of kinesiophobia in breast cancer women undergoing surgical treatment - Malchrowicz-Mośko, Ewa; Nowaczyk, Piotr; Wasiewicz, Janusz; Urbaniak, Tomasz; Siejak, Wojciech; Rozmiarek, Mateusz; Czerniak, Urszula; Demuth, Anna; Aguirre-Betolaza, Aitor Martinez; Castañeda-Babarro, Arkaitz (Frontiers in Oncology, 2023)
Lifestyle-associated factors like physical activity (PA) play an important role in cancer prevention and oncology treatment outcomes. The aim of the study is to investigate the level of kinesiophobia (fear of movement) in breast cancer (BC) patients undergoing surgical treatment depending on socio-demographic variables, lifestyle before cancer diagnosis, stage and type of BC and comorbidities. We interviewed 285 women (132 patients from Greater Poland Cancer Center – age: 55.7±12.4; BMI: 26.7±4.7 and 153 healthy women from control group – age: 49.0±15.7; BMI: 25.7±4.0) using Polish adaptation of the Tampa Scale of Kinesiophobia (TSK). Research results show that women with BC suffer from kinesiophobia (>37 points) significantly. Approximately 3/4 of the surveyed women with BC did not know the World Health Organization (WHO) recommendations regarding the weekly dose of PA for healthy people and for people with cancer. Before cancer diagnosis more than a half of women (60%) performed PA in accordance with WHO recommendations. 7% less women performed PA during oncology treatment. Almost a half of patients are not physically active during cancer treatment and 1/5 of the respondents declared that they do not know yet if they will be physically active after oncology treatment. The level of kinesiophobia in BC women with comorbidities was the same as in the group of BC women without comorbidities. However, the highest levels of fear of movement have been observed among women with BC suffering also from osteoporosis, obesity and diabetes. In general, higher levels of kinesiophobia were reported among women in less advanced stages of the disease. There were no differences in the level of kinesiophobia depending on the type of BC (hormonally dependent luminal cancers vs. other types). The level of kinesiophobia did not differ between women who were physically active before BC diagnosis and women who were not. In terms of socio-demographic variables, we found one direct association between the level of kinesiophobia (pain) with age – the greater age, the higher level of pain kinesiophobia.